2009
DOI: 10.1016/j.hal.2009.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interspecies differences in growth and toxicity of Pseudo-nitzschia while using different nitrogen sources

Abstract: Clonal cultures of plankton are widely used in laboratory experiments and have contributed greatly to knowledge of microbial systems. However, many physiological characteristics vary drastically between strains of the same species, calling into question our ability to make ecologically relevant inferences about populations based on studying one or a few strains. This study included nineteen non-axenic strains of three species of the diatom Pseudo-nitzschia isolated primarily from the mid-Atlantic coastal regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
127
2
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(156 citation statements)
references
References 88 publications
18
127
2
9
Order By: Relevance
“…The DA cell quotas estimated from the two samples in which DA was detected together with a predominance of P. fraudulenta (% 98% of total Pseudo-nitzschia) were 0.002 and 0.120 pg cell À1 . These values are comparable to DA cell quotas obtained in cultures of P. fraudulenta by Rhodes et al (1998a,b) (maximum 0.03 pg cell À1 ) and Thessen et al (2009) (maximum 0.16 pg cell À1 ). Despite these low toxin levels, DA has been previously detected in phytoplankton net samples (up to 6.6 mg L À1 ) collected in San José Gulf and Nuevo Gulf, coinciding with high cell densities of P. fraudulenta (Sastre et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The DA cell quotas estimated from the two samples in which DA was detected together with a predominance of P. fraudulenta (% 98% of total Pseudo-nitzschia) were 0.002 and 0.120 pg cell À1 . These values are comparable to DA cell quotas obtained in cultures of P. fraudulenta by Rhodes et al (1998a,b) (maximum 0.03 pg cell À1 ) and Thessen et al (2009) (maximum 0.16 pg cell À1 ). Despite these low toxin levels, DA has been previously detected in phytoplankton net samples (up to 6.6 mg L À1 ) collected in San José Gulf and Nuevo Gulf, coinciding with high cell densities of P. fraudulenta (Sastre et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Rhodes et al, 1996;Villac et al, 1993;Thessen et al, 2009;Sahraoui et al, 2011). Environmental factors, such as ambient nutrient concentrations, temperature, salinity, irradiance, photoperiod and pH, have been known to influence and under some circumstances to induce DA production in laboratory culture experiments (Lelong et al, 2012;and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that actively dividing cells were producing increasing amounts of DA. This is contrary to the findings of most earlier studies which showed that the highest DA levels occured during the stationary growth phase, when cell division ceased (reviewed in Bates, 1998;Fehling et al, 2004;Thessen et al, 2009). Garrison et al (1992) reported that P. australis produced DA during the exponential phase, but concluded that the results could be biased due to the very dense starting inoculum, which might have stressed the algae and, hence, enhanced DA production.…”
Section: Discussioncontrasting
confidence: 87%
“…Other studies also have observed measurable levels of DA prior to the onset of stationary growth, e.g. in P. australis (Garrison et al, 1992), P. multiseries (Pan et al, 1996a;Radan, 2008;Thessen et al, 2009) and P. fraudulenta (Thessen et al, 2009). P. cuspidata even exhibited greater cellular DA in the exponential phase relative to stationary phase when N, not Si or P, was the macronutrient inducing the onset of stationary growth (Auro, 2007).…”
Section: Nutritional Physiologymentioning
confidence: 94%
“…Additional events consistent with DA toxicity have been identified. In 2002, 87 sea lions were found stranded on beaches from the border of the USA to Ensenada, on the Baja peninsula, and it was assumed that DA toxicity was the cause of this event (Herná ndez-Becerril et al, 2007 (Rhodes et al, 1998), Monterey Bay, California, USA (Wells et al, 2005) and Chesapeake Bay, Maryland, USA (Thessen et al, 2009) . No adverse biological effects were detected.…”
Section: Mexicomentioning
confidence: 99%